2013
DOI: 10.1002/wcc.214
|View full text |Cite
|
Sign up to set email alerts
|

Firm and industry adaptation to climate change: a review of climate adaptation studies in the business and management field

Abstract: Firms and industries will have a central role in supporting societal adaptation to the physical impacts of climate change, especially in more directly affected sectors such as agriculture, forestry, construction, or transportation. However, the business and management field has repeatedly been criticized for its lack of engagement with climate change as a pressing issue, and adaptation to the physical impacts of climate change in particular. Our review of adaptation studies in the business and management field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(133 citation statements)
references
References 90 publications
5
124
0
4
Order By: Relevance
“…The literature increasingly seeks to unpack the detailed drivers that motivate economic agents to adapt or prevent them from doing so (Averchenkova et al, 2016;Hertin, Berkhout, Gann, & Barlow, 2003;Agrawala et al, 2011;Galbreath, 2011;Berkhout, 2012;Linnenluecke et al, 2013;Pauw & Pegels, 2013;Pauw, 2015). While the primary motive of firms may be to keep down costs, minimize disruptions or increase sales, the way the relevant decisions are taken is influenced by a range of additional factors.…”
Section: The Adaptation Behavior Of Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature increasingly seeks to unpack the detailed drivers that motivate economic agents to adapt or prevent them from doing so (Averchenkova et al, 2016;Hertin, Berkhout, Gann, & Barlow, 2003;Agrawala et al, 2011;Galbreath, 2011;Berkhout, 2012;Linnenluecke et al, 2013;Pauw & Pegels, 2013;Pauw, 2015). While the primary motive of firms may be to keep down costs, minimize disruptions or increase sales, the way the relevant decisions are taken is influenced by a range of additional factors.…”
Section: The Adaptation Behavior Of Firmsmentioning
confidence: 99%
“…Much of the relevant literature has focused on the private sector in developed countries (e.g., Linnenluecke, Griffiths, & Winn, 2013;Agrawala et al, 2011) and on larger firms (e.g., Averchenkova, Crick, Kocornik-Mina, Leck, & Surminski, 2016). Yet micro, small and medium enterprises (SMEs) 1 are highly vulnerable to climate change and they dominate the enterprise landscape in both developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…The most dominant adaptation focus within which systematic reviews have penetrated has been reviewing lessons from, and trends in, adaptation governance (Hardee and Mutunga 2010;Berrang-Ford et al 2011;Ford et al 2011;Pearce et al 2011;Ford et al 2012a, b;Larsen et al 2012;Murtinho and Hayes 2012;Biesbroek et al 2013;Kamau and Mwaura 2013;Vink et al 2013). Systematic reviews have not been restricted to this focus, however, with articles considering tourism (Kajan and Saarinen 2013), business management (Linnenluecke et al 2013), transport (Eisenack et al 2012), urban planning (Bowler et al 2010), human displacement (McLeman 2011;McDowell 2013), human management of ecosystem services (Heller and Zavaleta 2009;Charlton and Arnell 2011;Kolstrom et al 2011;Shepard et al 2011), and case studies of generalized adaptation research (Murtinho and Hayes 2012;Ford et al 2012a, b).…”
Section: Systematic Review For Adaptation Research: Challenges and Comentioning
confidence: 99%
“…Consideration of context, processes, and mechanisms of causality may require more time commitment per document than extraction of key estimates or discrete items of information. Many realist or in-depth reviews, for example, are conducted using fewer than 50 articles, often 30-40 documents (Bouzid et al 2013;Cheng and Berry 2013;Kajan and Saarinen 2013;Linnenluecke et al 2013), and even in-depth qualitative systematic analyses with as few as 15-20 articles (Walker et al 2011;Toloo et al 2013). Research has shown that systematic review of complex and heterogeneous literature bases cannot rely solely on strict keyword searches (Greenhalgh and Peacock 2005), and this is likely to apply to many complex adaptation policy and practice questions.…”
Section: Literature and Information Sourcesmentioning
confidence: 99%
“…Kirchhoff et al, 2013;Pilli-Sihvola et al, 2014;Soares and Dessai, 2016). Typically deeper co-operation with suppliers and users and demand-or user-driven approaches (McNie, 2013;Lourenço et al, 2015;McGregor, 2015) are suggested as measures to address these challenges of the production and use of climate information.…”
Section: Introductionmentioning
confidence: 99%